Desire, need and reality: Education and professionalization of elite groups in Brazil - Thais Joi Martins; Julio Cesar Donadone (Ciências Sociais Unisinos)
The objective of this paper is to report a study carried out at three Brazilian universities addressing only production engineering undergraduate courses. We sought to locate agents that had the same professional education to identify their different social positions, struggles, and disputes. The reason is based on the hypothesis that the students enrolled in the same university course, such as a prestigious engineering university course, are marked by different trajectories that may depend on symbolic capitals (cultural and economic) and the social origin and life trajectory of these students and of future graduates.